Multi-parameter joint analysis of the quality of honey - Yang Yuan; Changshi Ren; Mengqing Deng; Tian Zhao; Yan Liao; Rongqing Ren; Hua Wang; Yinchen Wang (Frontiers in Sustainable Food Systems, 2024)
The antioxidant activity of honey is mainly evaluated based on its phenolic acid and total flavonoid content, while other parameters are not considered important. The purpose of this study is to comprehensively evaluate the impact of honey's physicochemical indicators and the altitude of the collection site on its quality. This study measured physical and chemical indicators in Dalbergia hainanensis Merr. et Chun honey (DH), blueberry honey (BH), Eriobotrya japonica Lindl. honey (EH), and Rhus chinensis Mill. honey (RH) and then combined them to comprehensively analyze the influencing factors of honey's antioxidant capacity using correlation analysis, principal component analysis (PCA), and regression analysis. The results showed that the 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulfonate) (ABTS+) clearance ability of DH (17.60 ± 4.61 mg/ml) was significantly better than the other three varieties of honey (p <0.05). The results of the correlation analysis showed that the IC50 of the ABTS+ clearance rate was significantly negatively correlated with total flavonoid, Vitamin B1 (VB1), and Vitamin C (VC) content, as well as the a* and b * values, while positively correlated with elevation. The PCA results showed that the principal components (PCs) with eigenvalues exceeding 1 explained 86.28% of the variation. The IC50 of the ABTS+ clearance rate and altitude play an essential role in PC1, suggesting that two indicators are important in distinguishing different honeys. The regression analysis showed that total flavonoid and Vitamins B1 and C content, as well as elevation, are indispensable parameters affecting the antioxidant properties of honey. These results provide a reference method for evaluating the quality of honey from different places and altitudes.